Risk Factor for Stunting in Toddlers Aged 24-59 Months in Kersana Public Health Center Working Area - Novita Dewi Siti Shiyami; Mardiana (Universitas Airlangga, 2025)
According to the Indonesia Nutrition Status Survey 2022, Central Java highest stunting rate is in Brebes District. In Brebes Regency, the prevalence of stunting increased by 2.8% between 2021 and 2022. The goal of the study was to investigate the risk factors for stunting in toddlers in the Kersana Public Health Center area between the age of 24 and 59 months. This study employed a quantitative approach using a case-control design. Purposive sampling was used to create a sample set of 90. There are two variables in this study, namely the dependent variable (stunting) and the independent variables (family income, mother and father education, immunization, LBW, PBL, birth spacing, mother SEZ status during pregnancy, environmental sanitation, energy and protein intake, IMD, exclusive breastfeeding, complementary feeding, history of diarrhea and respiratory tract infections). The binary logistic regression test on multivariate analysis and the chi-square test were utilized in the bivariate analysis test. The study findings indicated that the following variables were linked to the incidence of stunting: immunization status (p-value=0.000), family income (p-value=0.000), environmental sanitation (p-value=0.000), history of diarrhea (p-value=0.030), early breastfeeding initiation history (p-value=0.006), history of exclusive breastfeeding (p-value=0.003), history of complementary feeding (p-value=0.000), energy intake (p-value=0.000), and protein intake (p-value= 0.001). According to the research, immunization status and energy intake are the two risk variables that have the most significant effects on stunting in children between the ages of 24 and 59 months.